Age Differences in Arterial and Venous Extra-Cerebral Blood Flow in Healthy Adults: Contributions of Vascular Risk Factors and Genetic Variants - Raz, Naftali (Brain Struct Funct, 2017)
Sufficient cerebral blood flow (CBF) and venous drainage are critical for normal brain function and their alterations can affect brain aging. However, to date, most studies focused on arterial CBF (inflow) with little attention paid to the age differences in venous outflow. We measured extra-cerebral arterial and venous blood flow rates with phase-contrast MRI and assessed the influence of vascular risk factors and genetic polymorphisms (ACE Insertion/Deletion, COMT val158met, and APOEε4) in 73 adults (age 18–74 years). Advanced age, elevated vascular risk, ACE Deletion, and COMT met alleles were linked to lower in- and outflow, with no effects of APOE ε4 noted. Lower age-related CBF rate was unrelated to brain volume and was observed only in val homozygotes of COMTval158met. Thus, in a disease-free population, age differences in CBF may be notable only in persons with high vascular risk and carriers of genetic variants associated with vasoconstriction and lower dopamine availability. It remains to be established if treatments targeting alleviation of the mutable factors can improve the course of cerebrovascular aging in spite of the immutable genetic influence.